METHODS OF ORGANIZING THE WORK OF THE CLASS LEADER (American Journal of Pedagogical and Educational Research, 2023)
Methods of working with parents and improving their legal literacy, recreational and psychotherapeutic tasks, methods of organizing the first parents' class meeting are explained.